2013
DOI: 10.2147/ott.s45906
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study analyzing survival and safety of bevacizumab/carboplatin/paclitaxel and cisplatin/pemetrexed in chemotherapy-naïve patients with advanced non-squamous bronchogenic carcinoma not harboring EGFR mutation

Abstract: PurposeThe majority of Egyptian patients with lung cancer present at a late stage of the disease. Bevacizumab/carboplatin/paclitaxel, as well as cisplatin plus pemetrexed, are both standard regimens for advanced non-squamous bronchogenic cancer. This study compares both regimens, in terms of efficacy and toxicity profile, in Egyptian patients.Patients and methodsThis is a randomized Phase II study comparing toxicity profile and survival in 41 chemotherapy-naïve patients with stage IIIB or IV non-squamous NSCLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…As VEGF has been implicated in the same signaling cascades with TF as EGFR, we sought to determine whether bevacizumab therapy would influence our results. Bevacizumab adjuvant treatment in particular has been linked with increased thrombotic risk [33,61,62]. Multivariate analysis demonstrated there was not a statistically significant difference in our results when controlling for bevacizumab therapy (Table 3).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…As VEGF has been implicated in the same signaling cascades with TF as EGFR, we sought to determine whether bevacizumab therapy would influence our results. Bevacizumab adjuvant treatment in particular has been linked with increased thrombotic risk [33,61,62]. Multivariate analysis demonstrated there was not a statistically significant difference in our results when controlling for bevacizumab therapy (Table 3).…”
Section: Discussionmentioning
confidence: 68%
“…One study by Dou et al investigated EGFR mutation status and demonstrated an increased VTE risk in EGFR wild-type adenocarcinoma patients [66]. Other studies investigating anti-EGFR treatments have also noted an increased rate of thrombosis [33,61,62,[67][68][69][70]. The split consensus for the role of EGFR in NSCLC-associated VTE described above may explain why studies that focused on EGFR in other malignancies have not shown conclusive results.…”
Section: Discussionmentioning
confidence: 99%
“…For advanced NSCLC without driver gene alterations, such as those in EGFR, KRAS, ALK, ROS1 and BRAF, platinum-based doublet chemotherapy is considered to be the most common standard first-line treatment approach ( 4 ). In patients with advanced non-squamous carcinoma NSCLC, the treatment can be combined with bevacizumab and maintained with pemetrexed or bevacizumab following standard therapy ( 5 7 ). For patients with driver gene alterations, targeted therapy is often the first treatment approach, since the relevant agents can improve overall survival (OS) and the overall response rate (ORR).…”
Section: Introductionmentioning
confidence: 99%